Experimental Study of Instabilities and Secondary Effects of a Ground Vortex Flow - Barata, Jorge M M (2012)
Laser-Doppler measurements of velocity characteristics of the flowfield resulting from the collision of a wall jet with a boundary layer are presented and discussed together with visualization of the flow. The experiments have been carried out for boundary layer to wall jet velocity ratios of 0.5 and 0.58. Direct photography, digital film imaging, and mean and turbulent laser Doppler measurements were obtained to characterize this type of flows. For the present conditions the results revealed the existence of a small counter-rotating recirculating zone located upstream the separation point not yet reported before for this type of flows. The results show that this secondary vortex has a similar oscillating behavior observed in some configurations leading to ground vortex flows, where they are also probably present, but due the geometric and characteristic parameters could not be identified separately. A particular ordered sequence was recognized for the small recirculation zone, and can be confirmed by the bimodal histogram of the horizontal velocity measurements obtained. In spite of the apparent organized sequence of the turbulent structure of the collision zone, the power spectra measurements did not exhibit any evident particular peaks.